Studi Kasus Dampak Perilaku Bullying Terhadap Perkembangan Sosial Emosional Anak Tk B Di Tk Al Azzam Ternate Maluku Utara - Kasiati, Kasiati; Al Jufri, Lubna; Pertiwi, Hikmah; Gustina, Hera; Daisu, Konny Fransiska; Sudarya, Agus (Jurnal Pendidikan Indonesia, 2022)
All parents want their children to be safe in school, and all educators and education providers want a safe school environment for students studying in this school. It's a bit strange that almost everyone seems to know about bullying, but often lets it happen. They exclude cases of bullying in schools as if bullying is different from other cases of violence. This article tries to look at bullying from different perspectives, trying to find different answers about how to deal with bullying from the perspective of parents, educators and children related to bullying.